Madrasah Ibtidaiyah Teachers' Strategies for Fostering Scientific Attitudes in Science Learning: A Case Study of State Madrasah Ibtidaiyah in Aceh Besar Regency - Abdullah, Maghfirah; Oviana, Wati; Jannah, Misbahul; Nor Fadzilah Binti Wan Husin, Wan (Jurnal keilmuan dan Kependidikan dasar, 2026)
Science learning in the Merdeka Curriculum emphasizes the development of scientific attitudes as an essential component of the learning process. Scientific attitudes are needed to cultivate students' carefulness, honesty, critical thinking, and curiosity toward the phenomena they study. This study aims to describe the role of teachers in fostering scientific attitudes in fifth-grade science learning at State Madrasah Ibtidaiyah (MIN) in Aceh Besar Regency, both at the planning and implementation stages of instruction. This study employed a qualitative descriptive method with a case study design. The research subjects consisted of three fifth-grade teachers from three State Madrasah Ibtidaiyah in Aceh Besar. Data were collected through observations, interviews, and documentation. The data were analyzed through the stages of data reduction, data display, and conclusion drawing. The findings indicate that teachers have made efforts to foster scientific attitudes in science learning; However, their implementation varies across schools and has not been consistently integrated into every learning activity. Scientific attitudes were reflected in observing, questioning, and discussion activities, with varying levels of intensity and depth depending on classroom conditions and teachers' instructional practices. Therefore, continuous reinforcement and habituation are needed to optimize the cultivation of scientific attitudes in science learning.